ENHANCING STUDENTS’ CRITICAL READING THROUGH LITERATURE CIRCLES IN CLASSROOM READING ACTIVITIES - Muhamad Taufik Ismail; Muhamad Suhaili (Sinar Lima, 2025)
Reading is an essential academic skill that enables students to comprehend, analyze, and evaluate information critically. However, observations at the English Language Education Program of Mandalika University revealed that many students struggled with identifying main ideas, analyzing arguments, and evaluating evidence in texts. One factor contributing to these difficulties was the monotonous method of teaching, which often led to low motivation. This study aimed to improve students' critical reading skills through the implementation of literature circles at the fourth-semester students in the English Language Education Program at Mandalika University of Education. The research applied classroom action research (CAR) with two cycles consisting of planning, acting, observing, and reflecting. The instruments used in this research were questionnaires and tests at the end of each cycle. The results indicate that literature circles significantly enhanced students' critical reading skills. The use of structured group roles facilitated deeper engagement with texts, encouraged peer collaboration, and improved students' analytical and evaluative reading abilities.